Access to Health in Border Areas: Literature Review - Asri Nur Aina; Kemal Sandi; Oky Nur Pratiwi Johansyah (Program Pascasarjana Universitas Negeri Makassar, 2023)
Communities living in border areas face greater challenges in terms of access to health compared to urban communities. This article aims to strengthen and complement previous research on health accessibility policies for people in border areas. This research is a literature review that uses the Publish or Perish (PoP) software to search for relevant articles, as well as the Vos viewer to visualize the relevance of previous research. A total of 19 relevant previous studies were used in this study. The results of the research show that people in border areas, both in Indonesia and other developing countries, face significant health access problems. The implication of this research is the importance for governments in developing countries to develop health policies that are applicable and in accordance with conditions in border areas.